MINERAL PROCESSING IMPACT ON WHEAT AND BARLEY (TIRY BREAD AND SAMOON AS AN EXAMPLE) - Nashmil Ali Abdul; Azhin Mahmood Abdulrahman; Sonia Talb; Huda Jamal Mhamad (Mesopotamia Journal of Agriculture)
Bread (Tiry and Samoon), a special and vital bread in a Kurdistan region- Iraq, which people consume daily in their meals. Tiry bread and Samoon contain some macro and micro minerals. Also, consumption of bread is the course of enter the heavy metals into food chain. In this study, wheat and barley flour is used to produce the Tiry bread and Samoon, and some macro and micro minerals in both (wheat and barley) flour and breads that produces them are indicated. In addition, the effect of minerals in bread and Samoon are displayed on human health in a long period. A total of 16 minerals were indicated from breads and flour by Inductive Coupled Plasma (ICP). The highest concentration of Fe, CD, Mn Zn, Cu, and Cr were obtained from barley Turkish flour (28.967, 0.035, 30.723, 20.445, 4.989 and 1.206 mg/kg). Furthermore, the highest V, Mo, B, Ba, and Sb were obtained from TBF (1.713, 1.01, 1.48, 4.038, 0.408 mg/kg). The results of the study showed that the concentration of (Fe, Cd, Mn, Zn, Pb, Se, Ni, Ci, Cr, V, Mo, B, Mg, Ba, Sb and As) in a limited range providing by FAO/WHO. Also, the daily intake and PTWi in some of them are high. but not higher than the range of limitation.